Recent advances in the genetics of amyotrophic lateral sclerosis and frontotemporal dementia: common pathways in neurodegenerative disease. - Talbot, K; Ansorge, O (2006)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease classically defined by the impairment of the voluntary motor system and ubiquitin-positive intraneuronal aggregates in anterior horn cells. Frontotemporal dementia (FTD) is a common form of neurodegenerative dementia and presents with personality change associated in a significant subgroup of patients with cortical ubiquitin-only neuropathology (FTD-U). Careful study of ALS as well as FTD patient cohorts suggests clinical as well as pathological overlap of ALS with FTD. The idea that this reflects a shared pathogenesis has received strong support from the identification of new genetic loci on chromosome 9p and of mutations in specific genes (CHMP2B and DCN1) in families with co-segregation of ALS and FTD. The identification of two further genetic causes of FTD-U with (rare) ALS (PGRN) or without ALS (VCP) also provides a starting point for exploring the pathways associated with ubiquitin-mediated protein mishandling in FTD-U and ALS. Pure ALS, through ALS with cognitive impairment and ALS-FTD to pure FTD-U, may represent a continuous spectrum of ubiquitin-associated neurodegenerative disease.